2010
DOI: 10.4049/jimmunol.1000842
|View full text |Cite
|
Sign up to set email alerts
|

STAT5 Is Critical To Maintain Effector CD8+ T Cell Responses

Abstract: During an immune response, most effector T cells die, whereas some are maintained and become memory T cells. Factors controlling the survival of effector CD4+ and CD8+ T cells remain unclear. In this study, we assessed the role of IL-7, IL-15, and their common signal transducer, STAT5, in maintaining effector CD4+ and CD8+ T cell responses. Following viral infection, IL-15 was required to maintain a subpopulation of effector CD8+ T cells expressing high levels of killer cell lectin-like receptor subfamily G, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
104
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(119 citation statements)
references
References 49 publications
(75 reference statements)
12
104
0
Order By: Relevance
“…33,43 Further, we have shown that a common g chain cytokine/STAT5/Bcl-2 network acts downstream of IL-7 and IL-15 to protect KLRG1 lo CD127 hi effector T cells from Bim and likely Puma, favoring memory cell development. 34 Third, as mentioned above, the massive expansion of effector and pre-memory subsets in Bim À / À mice severely restricts IL-15 availability for KLRG1 hi CD127 lo cells. As both KLRG1 hi C-D127 lo and KLRG1 lo CD127 hi cells express similar levels of CD122, it is unclear which subset contributes more to this population effect, although the sheer size of the KLRG1 hi CD127 lo compartment suggests a dominant role for this subset.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…33,43 Further, we have shown that a common g chain cytokine/STAT5/Bcl-2 network acts downstream of IL-7 and IL-15 to protect KLRG1 lo CD127 hi effector T cells from Bim and likely Puma, favoring memory cell development. 34 Third, as mentioned above, the massive expansion of effector and pre-memory subsets in Bim À / À mice severely restricts IL-15 availability for KLRG1 hi CD127 lo cells. As both KLRG1 hi C-D127 lo and KLRG1 lo CD127 hi cells express similar levels of CD122, it is unclear which subset contributes more to this population effect, although the sheer size of the KLRG1 hi CD127 lo compartment suggests a dominant role for this subset.…”
Section: Discussionmentioning
confidence: 95%
“…33 The huge size of the anti-LCMV CD8 þ T-cell response, even in WT mice, likely limits the effector response by restricting IL-15 availability. 34 Such IL-15 limitation likely enhances Puma expression in KLRG1 hi CD127 lo cells relative to KLRG1 lo CD127 hi cells as the latter cells can utilize both IL-7 and IL-15 for survival. 33 Further, we confirm and extend prior results, showing that Puma has a preferential effect on contraction of KLRG1 hi CD127 lo cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this important cell-autonomous transcriptional control of CD8 + T cell differentiation, extrinsic influences exerted by cytokines play a critical role in regulating CD8 + effector expansion, as well as survival. IL-15, either alone or together with IL-7, can promote the survival of SLECs and KLRG1 lo CD127 hi effector cells (12,16), respectively, during viral infections. IFN-g was shown to support the expansion of CD8 + effectors (17).…”
Section: Cd8 + T Cells Responding To Viral Infections Initiate Their mentioning
confidence: 99%
“…13 Bcl-2 levels in activated T cells are controlled by IL-7 and IL-15 signaling through STAT5, a molecule essential for effector CD8 þ T-cell survival. 18 However, the role of other anti-apoptotic Bcl-2 family members in effector T-cell apoptosis remains unclear.…”
mentioning
confidence: 99%